Guide to successful brickwork - Brick Development Association (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2021)
"The BDA guide to successful brickwork is the definitive practical guide to obtaining successful results in brickwork construction"--
OCLC-licensed vendor bibliographic record.
Keywords: Bricklaying; TECHNOLOGY / Construction / Masonry; TECHNOLOGY / Construction / Contracting